Transcriptional Patterns of Biogeochemically Relevant Marker Genes by Temperate Marine Bacteria - Alonso-Sáez, Laura; Morán, Xosé Anxelu G.; González, José M. (Frontiers in Microbiology, 2020)
Environmental microbial gene expression patterns remain largely unexplored, particularly at interannual time scales. We analyzed the variability in the expression of marker genes involved in ecologically relevant biogeochemical processes at a temperate Atlantic site over two consecutive years. Most of nifH transcripts, involved in nitrogen (N) fixation, were affiliated with the symbiotic cyanobacterium Candidatus Atelocyanobacterium thalassa, suggesting a key role as N providers in this system. The expression of nifH and amoA (i.e., marker for ammonia oxidation) showed consistent maxima in summer and autumn, respectively, suggesting a temporal succession of these important N cycling processes. The patterns of expression of genes related to the oxidation of carbon monoxide (coxL) and reduced sulfur (soxB) were different from that of amoA, indicating alternate timings for these energy conservation strategies. We detected expression of alkaline phosphatases, induced under phosphorus limitation, in agreement with the reported co-limitation by this nutrient at the study site. In contrast, low-affinity phosphate membrane transporters (pit) typically expressed under phosphorus luxury conditions, were mainly detected in post-bloom conditions. Rhodobacteraceae dominated the expression of soxB, coxL and ureases, while Pelagibacteraceae dominated the expression of proteorhodopsins. Bacteroidetes and Gammaproteobacteria were major contributors to the uptake of inorganic nutrients (pit and amt transporters). Yet, in autumn, Thauma- and Euryarchaeota unexpectedly contributed importantly to the uptake of ammonia and phosphate, respectively. We provide new hints on the active players and potential dynamics of ecologically relevant functions in situ, highlighting the potential of metatranscriptomics to provide significant input to future omics-driven marine ecosystem assessment.